Digital Marketing and Product Variation on Purchase Decisions Moderating by Packaging - Agustini Tanjung; Nur Aeni; Vivian R. Mangahas Mangahas (DEAL: International Journal of Economics and Business, 2023)
Consumer lifestyle in choosing products is more a simple and practical. The practicality of what consumers do is seen in consuming drinks for accompany many activities, coffee as a sample. Coffee is loved by many people. This research tested about 164 respondents, who had bought and consumed Good Day in Bekasi Regency and data collection was carried out through a questionnaire using the google form. This research aims to examine digital marketing and product variations on purchasing decisions moderated by packaging on Good Day products in Bekasi Regency. Primary and secondary data sources are used to support this research and used quantitative research. The results of this research show that: 1. Digital marketing of Good Day coffee products in Bekasi Regency is stated to have a relatively small influence (30%) so that it can encourage consumer purchasing decisions, 2 . The variety of Good Day coffee products in Bekasi Regency is stated to have a relatively small influence (44%) so that it can encourage consumer purchasing decisions. 3. Digital marketing which is moderated by Good Day product packaging in Bekasi Regency has an influence of (-10%) so it does not encourage consumer purchasing decisions, 4. Product variations moderated by Good Day packaging in Bekasi Regency have an influence of (10%)